Modelling of Fluid Flow and Cuttings Transport in Horizontal Narrow Annulus - OFEI, TITUS NTOW (2017)
The motivation for this research originated from the little understanding on the phenomenon of cuttings and liquid flow in narrow horizontal wellbore. The study was aimed at modelling single-phase yield power law (YPL) fluid flow and two-phase (cuttings-water, cuttings-power law, and cuttings-YPL) flow through narrow horizontal annulus. The effects of drillpipe rotation speed, eccentricity, diameter ratio, and fluid rheological properties were investigated on the flow velocity and viscosity profile distributions, annular pressure losses, and cuttings concentration. The modelling was performed using a computational fluid dynamics (CFD) software, ANSYS CFX-14. The slot approximation technique was adopted to formulate a new approximate pressure loss model for YPL fluid with drillpipe rotation. The Buckingham-